2008
DOI: 10.1159/000165114
|View full text |Cite
|
Sign up to set email alerts
|

Case Fatality of Stroke and Day of the Week: Is the Weekend Effect an Artifact?

Abstract: Background and Purpose: For stroke admissions, the ‘weekend effect’ has been associated with higher stroke fatality. However, it is unclear if stroke case fatality shows this pattern if the onset day is taken into account. Day of the week variation in stroke case fatality was examined using 16-year stroke registration data. Design and Methods: Data were obtained from Takashima Stroke Registry in central Japan. There were 1,578 registered first-ever cerebral infarction and cerebral hemorrhage stroke cases durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…15 Our study eliminated this artifact by only including emergency room admissions and excluding hospital transfers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Our study eliminated this artifact by only including emergency room admissions and excluding hospital transfers.…”
Section: Discussionmentioning
confidence: 99%
“…8 We only included emergency room admissions for stroke to eliminate the artifact from patients transferred from other hospitals on days other than their day of admission that was found in the Takashima Stroke Registry study. 15 We chose to only study ischemic stroke, because there have been previous studies using the NIS database to analyze a weekend effect on intracerebral hemorrhage 16 and subarachnoid hemorrhage. 17 Interestingly, in this present study, we found that weekend patients with stroke were slightly more likely to receive thrombolytics but there was no difference in in-hospital mortality, which is similar to the findings from the Virginia Patient Data System.…”
Section: Discussionmentioning
confidence: 99%
“…This was the reason we chose to use the 7-day case fatality indicator [21] to analyze the impact of season on fatality. We also used the conventional method of identifying case fatality, the 28-day case fatality [16] .…”
Section: Methodsmentioning
confidence: 99%
“…19,20 Some authors argued that the weekend effect might be an artifact because the tendency toward a higher weekend fatality disappeared when stroke onset time, and not hospital admission time, was taken into account by eliminating the bias of the potential exclusion of nonfatal cases having deferred admission. 41 Finally, other studies, some of which specifically focused on patients treated with thrombolysis, did not observe a night or weekend effect. [25][26][27][28][29] All those studies were conducted in single or few centers in a single country and hence were at risk for center effects, and their results could not be generalized.…”
Section: Discussionmentioning
confidence: 98%